Contact heat transfer of a cutting diamond wheel with a boundary layerof air. Issue 1 (June 2021) - Bespalova, A; Faizulyna, O; Lebedev, V; Frolenkova, O; Chumachenko, T
Abstract: Cutting of natural and artificial building materials is most often carried out with diamond cutting wheels on a metal base at cutting speeds of about 50-80 m/s. The intensity of the cutting process causes a significant heat release, as a result of which the wheel temperature rises to unacceptable values. The value of these unacceptable temperatures is about 600 - 650°C At these temperatures, graphitization of diamond grains occurs, i.e. loss of diamond layer and loss of cutting properties. In addition, a thin diamond wheel (thickness 1 - 3 mm) is deformed, which leads to jamming and its tensile strength at these temperatures is reduced by half, which creates the risk of rupture by centrifugal forces. In this work, it is taken into account that during the rotation of the wheel, a boundary layer of air is created around it, which is stationary relative to the wheel. Consequently, contact heat transfer occurs between the wheel and the boundary layer, and then convective heat transfer occurs between the boundary layer and the surrounding air. This scheme allows you to more accurately determine the time of safe operation of the diamond wheel. Contact heat transfer between the wheel and the boundary layer is not effective enough to lower the temperature. When air with a negative temperature is introduced into the boundary layer by means of a Rank-Hillsch tube, the wheel temperature decreases by about 10%. When a sprayed coolant (fog cooling) is introduced into the boundary layer by means of an ejector tube, the wheel temperature decreases by 25%, which ensures an increase in the time of continuous operation.